THE USE OF SCAFFOLDING IN TEACHING SPEAKING - Mulyana, Agus (2012)
This research attempts to uncover scaffolding strategies utilized by the English teacher in improving learners' speaking skills. This study was conducted at a Junior High School in Garut, West Java. It specifically attempts to investigate what types of scaffolding, to investigate the most frequently applied type of scaffolding, and reasoning or theoretical foundations of language leaning underpinning his such determinate types of scaffolding. This study used descriptive method; it employed a qualitative case study design. The data were collected through classroom observations and interview. Classroom observations were videotaped and transcribed, categorized, and interpreted to answer the research questions. The results of classroom observation were the basis for conducting interview. And subsequently, the interview was audio taped, transcribed. The transcriptions were analyzed through coding and categorization to interpret the data. There appeared to be some evidence of scaffolding from classroom observation, namely: game, stating goal, work in pairs, gesture, verifying and clarifying students' understanding, motivating, error corrections, modeling, drilling, explaining, and doing elicitation. The most frequently applied type of scaffolding the English teacher utilized was elicitation. The students had limited opportunities outside of class to practice speaking. The students who were reluctant and highly infrequently communicating in English needed teacher's support and assistant. Doing elicitation was considered effective, successful, feasible for learners' language acquisition. There appeared to be some reasons behind the use of scaffolding. Firstly, language learners need opportunities to acquire the target language and get involved in meaningful communicative events. They need exercises which enable them to attain communicative objectives of the curriculum, engagement in communication, and require the use of such communicative processes as information sharing, negotiation of meaning, and interaction. Secondly, language learners need an enjoyable and more relax classroom learning atmosphere. Thirdly, to foster language learners' development, the language learners need a great deal of exposure to real-life English use. It is the language the teachers use in the classroom as the major source of comprehensible target language input. It is important for language learners to listen to as much English in meaningful context. Despite the fact that this study provides evidence of the issue being investigated and might be useful for basic information for further research, the finding is not exhaustive since a limited number of observations were merely allowed to be conducted due to the factors provided for conducting this study. This study only covers very limited areas and discusses certain points. Therefore, further studies are needed for comprehensive understanding about scaffolding strategies in accordance with L2 speaking.